FAMILY RESILIENCE IN ISLAMIC PERSPECTIVE (A CASE STUDY OF PARENT AND CHILD INTERACTION BEHAVIOR IN THE DISTRICT OF SOMBA OPU GOWA) - Rahman R, Abd (Jurnal Adabiyah, 2020)
This paper discusses the interaction behavior of parents and children, facing problems in carrying out the duties and roles of the child's parents as the person in charge and the first teacher of understanding and practicing children's religiosity. This paper aims to find and describe the interaction patterns of children's parents, constraints and challenges in carrying out their duties as the first teacher in the family and effective efforts to foster children in the family. This paper is qualitative descriptive, with deductive-inductive methods. Data relying on primary sources through observation and interviews, and is complemented by secondary data obtained from literature. This paper shows the relationship between interaction behavior, the position of father and mother and child with family resilience through internalization of religious norms and values, understanding and practicing the teachings of the faith, praying five times a day, and noble morals. Parent and child interactions are temporal in nature, depending on the conditions of parents and children in the process of interaction in the family. The routine and personality activities of parents who are competent in understanding Islam are relatively constraints and challenges in the interaction between parents and children in carrying out their functions, the role of being the first teacher in the family. This paper is an indicator and motivator that encourage family life to foster children in understanding and practicing the principles of Islam. Keywords: Family resilience, behavior, interaction, parents of children, Islam.تناقش هذه الورقة السلوك التفاعلي بين الوالدين والأطفال، حيث يواجهون مشاكل في أداء واجبات وأدوار والدي الطفل بصفته الشخص المسؤول والمعلم الأول لفهم تدين الأطفال وممارسته. تهدف هذه الورقة إلى إيجاد ووصف أنماط التفاعل بين أولياء أمور الأطفال، والقيود والتحديات في أداء واجباتهم كأول معلم في الأسرة والجهود الفعالة لرعاية الأطفال في الأسرة. هذه الورقة وصفية نوعية، مع الأساليب الاستنتاجية الاستقرائية ، والبيانات التي تعتمد على المصادر الأولية من خلال الملاحظة والمقابلات وتكملها البيانات الثانوية التي تم الحصول عليها من الأدب. توضح هذه الورقة العلاقة بين السلوك التفاعلي، وموقع الأب والأم والطفل في المرونة الأسرية من خلال استيعاب الأعراف والقيم الدينية، وفهم وممارسة تعاليم الدين، والصلاة خمس مرات في اليوم، والأخلاق النبيلة. تفاعلات الوالدين والطفل مؤقتة بطبيعتها ، حسب ظروف الوالدين والأطفال في عملية التفاعل في الأسرة. تعتبر الأنشطة الروتينية والشخصية للآباء المؤهلين في فهم الإسلام قيودًا وتحديات نسبية في التفاعل بين الآباء والأطفال في أداء وظائفهم، ودور كونهم المعلم الأول في الأسرة. تعتبر هذه الورقة مؤشرا ومحفزا يشجع الحياة الأسرية لتنشئة الأبناء على فهم مبادئ الإسلام وممارستها.Tulisan ini membahas tentang perilaku interaksi orang tua dan anak, menghadapi problema dalam menjalankan tugas dan peran orang tua anak sebagai penanggung jawab dan guru pertama terhadap pemahaman dan pengamalan relegiutas anak. Tulisan ini bertujuan untuk menemukan dan mendeskripsikan  pola interaksi orang tua anak, kendala dan tantangan dalam mengemban tugasnya sebagai guru pertama dalam keluarga serta upaya yang efektif pembinaan anak-anak dalam keluarga. Tulisan ini bersifat deskriftif kualitatif, dengan metode deduktif-induktif, data disandarkan kepada sumber primer melalui observasi, wawancara dan dilengkapi oleh data sekunder yang diperoleh dari leteratur. Tulisan ini menunjukkan kaitan perilaku interaksi, posisi ayah dan ibu serta anak dengan ketahanan keluarga melalui internalisasi norma dan nilai agama, pemahaman dan pengamalan ajaran akidah, salat lima waktu, serta akhlak mulia. Interaksi orang tua dan anak bersifat temporal, tergantung pada kondisi orang tua dan anak dalam proses interaksi dalam keluarga. Kesibukan rutinitas dan kepribadian` orang tua yang bersifat kompetensi pemahaman terhadap Islam relative menjadi faktor kendala dan tantangan dalam interaksi orang tua dan anak dalam menjalankan  fungsi, peran sebagai guru pertama dalam keluarga. Tulisan ini menjadi indikator dan motivator yang mendorong kehidupan keluarga untuk pembinaan anak-anak dalam pemahaman dan pengamalan ajaran-ajaran prinsip dalam Islam.